More answers

2x+3 = 9x 3 = 9x-2x = 7x 7x = 3 x = 3/7

Q: Solve 2x plus 3 equals 9 x equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

-2x+14=20 -2x=20-14 -2x=6 -2x/-2=6/-2 x=-3

88+x=3x+22 88=2x+22 66=2x x=33

the converse of this conditional is true

if 2x+3=9 then 2x=6 so x=3

Then x = 6 Therefore; 5x + 3 = 33 First you have to solve the value of X: 8X + 5X + 2X +4X = 114; OR 19x = 114. When you divide both sides of the equation by 19 to solve for X, you find that X = 6. Ergo, 5X + 3 = 30 + 3 = 33; hence, 5X + 3 = 33.

Related questions

3

2x+3 = 7 2x = 7-3 2x = 4 x = 2

4x + 3 = -3 + 2x + 14 2x + 3 = -3 +14 2x + 3 = 11 2x = 8 x=4

2x+3 = -11 2x = -11-3 2x = -14 x = -7

3x+4 = 2x-3 3x-2x = -3-4 x = -7

(3,3)

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

3x-2 = 2x+3 3x-2x = 3+2 x = 5

2x + 3 = 9x Subtract 2x from both sides: 3 = 7x Divide both sides by 7: 3/7 = x

2x + 3 = x 2x + 3 - 3 = x - 3 2x = x - 3 2x - x = x - 3 - x x = -3

2x + 2/3= 5/3 2x= 3/3 2x=1 x=1/2

2x + 3 = 9 To solve Subtract '3' from both sides 2x = 6 Divide both sides by '2' x = 3 The Answer!!!!!